Protective effects of inhalation of essential oils from Mentha piperita leaf on tight junctions and inflammation in allergic rhinitis - Park, Nayoung; Chung, Jae Yoon; Kim, Mi Hye; Yang, Woong Mo (Frontiers in Allergy, 2022)
Allergic rhinitis is one of the most common diseases, which is caused by IgE-mediated reactions to inhaled allergens. Essential oils from the Mentha piperita leaf (EOM) are known to be effective for various diseases, such as respiratory diseases. However, the effect of inhalation of EOM on tight junctions and inflammation related to allergic rhinitis is not yet known. The purpose of this research was to explain the effects of the inhalation of EOM on tight junctions and inflammation of allergic rhinitis through network pharmacology and an experimental study. For that purpose, a pharmacology network analysis was conducted comprising major components of EOM. Based on the network pharmacology prediction results, we evaluated the effect of EOM on histological changes in mice with ovalbumin and PM10-induced allergic rhinitis. Allergic symptoms, infiltration of inflammatory cells, and regulation of ZO-1 were investigated in mice with allergic rhinitis. Other allergic parameters were also analyzed by reverse transcription polymerase chain reaction and western blot in nasal epithelial cells. In the network analysis, the effects of EOM were closely related to tight junctions and inflammation in allergic rhinitis. Consistent with the results from the network analysis, EOM significantly decreased epithelial thickness, mast cell degranulation, goblet cell secretion, and the infiltration of inflammatory cells in nasal tissue. EOM also regulated the MAPK-NF-κB signaling pathway, which was related to tight junctions in nasal epithelial cells. This research confirmed that inhalation of EOM effectively restores tight junctions and suppresses inflammation in the allergic rhinitis model. These results reveal that EOM has a therapeutic mechanism to treat allergic rhinitis.